Rubens in private : the master portrays his family ; [... on the occasion of the Exhibition "Rubens in Private. The Master Portrays his Family", ... at the Rubenshuis, Antwerp, 28 March - 28 June 2015] - Beneden, Ben van; Beneden, Ben van; Rubens, Peter Paul (Thames & Hudson, 2015)
Michelangelo regarded portraiture as a trivial genre, and Peter Paul Rubens did not instantly develop a preference for it either. Yet Rubens succeeded, as none other, in endowing his portraits with an almost palpable sense of immediacy, and was to become one of the greatest portraitists of all time. His most beautiful and surprising portraits are those of his immediate family. These intimate pictures were not intended for public display and are therefore considerably freer and more experimental than the likenesses he painted of influential patrons. Nothing about these private images seems idealized. They are uncommonly honest and veracious and at the same time expressive of great tenderness. While the hundreds of letters he wrote reveal very little about his emotional life, Rubens's portraits of family members testify in a special way to the affection he felt for his first and second wives, his brother and his children. Nearly four hundred years after they were painted or drawn, Rubens's family portraits are still full of life. This comprehensive exhibition is the first ever dedicated to the private work of the most public painter of the seventeenth century. Taking a fresh look at Rubens's most intimate works, it re-examines their functions and meanings, and reconsiders them in the context of the master's life and his social and artistic concerns.0Exhibition: Rubenshuis, Antwerp, Belgium (28.03. - 28.06.2015)